CURRENCY DEPRECIATION AND CORPORATE NET WORTH OF LISTED COMPANIES IN INDONESIA - A. Prasetyantoko (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2008)
This paper is concerned with the impact of currency depreciation during the period of crisis on the corporate net worth of listed companies in Indonesia. The findings can shed light on the corporate “balance sheet effect” of currency crisis. This paper finds that firms with a higher debt-equity ratio have a lower value in market capitalization growth, sales and asset during crisis and in postperiod of crisis. Meanwhile, firms with majority foreign ownership (F) have higher sales during crisis and in one year after crisis than domestic companies (L). Furthermore, firms in tradable sector (T) have higher sales and less debt-equity ratio during crisis and one year after crisis than those in Non-tradable sector (N). This research uses data from Indonesian Stock Exchange’s (IDX) database and ECFFN covering the period of 1994-2004. This empirical research using panel data analysis includes 238 listed companies with at least 5 consecutive years.